2014
DOI: 10.1016/j.medengphy.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Screening of obstructive sleep apnea with empirical mode decomposition of pulse oximetry

Abstract: Detection of desaturations on the pulse oximetry signal is of great importance for the diagnosis of sleep apneas. Using the counting of desaturations, an index can be built to help in the diagnosis of severe cases of obstructive sleep apnea-hypopnea syndrome. It is important to have automatic detection methods that allows the screening for this syndrome, reducing the need of the expensive polysomnography based studies. In this paper a novel recognition method based on the empirical mode decomposition of the pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 40 publications
0
36
0
3
Order By: Relevance
“…However, previous studies reported that the ODI was useful in OSA because it closely correlated with the AHI and had potential for facilitating the accurate diagnosis of OSA with high sensitivity and specificity. 48, 49 Moreover, a previous clinical study demonstrated that the cut-off value to predict an AHI of >5, >15, and >30 events/h with high accuracy was an ODI of >5, >15, and >30 events/h, respectively. 50 Third, patients were diagnosed with sleep apnea according to the AHI based on polysomnography, whereas the AHI during CPAP was extracted from a smart card attached to the device, and the 2 AHIs were compared: before and during CPAP treatment.…”
Section: Study Limitationsmentioning
confidence: 97%
“…However, previous studies reported that the ODI was useful in OSA because it closely correlated with the AHI and had potential for facilitating the accurate diagnosis of OSA with high sensitivity and specificity. 48, 49 Moreover, a previous clinical study demonstrated that the cut-off value to predict an AHI of >5, >15, and >30 events/h with high accuracy was an ODI of >5, >15, and >30 events/h, respectively. 50 Third, patients were diagnosed with sleep apnea according to the AHI based on polysomnography, whereas the AHI during CPAP was extracted from a smart card attached to the device, and the 2 AHIs were compared: before and during CPAP treatment.…”
Section: Study Limitationsmentioning
confidence: 97%
“…Azarbarzin and Moussavi [97] developed a CAD method based on LDA where zero-crossing rate and peak frequency were calculated from snoring sound signals. Schlotthauer et al [98] used empirical mode decomposition of pulse oximetry signals for automated OSAS screening. Varon et al [99] proposed principal components of the QRS complexes as features for detecting OSA.…”
Section: Sleep Disorders Diagnosismentioning
confidence: 99%
“…The estimated AHI reaches the highest Acc for the three thresholds, outperforming ODI 3 in AHI = 5 and 30 e/h. [17]. Our proposal achieved an overall higher diagnostic ability than those reported in these works.…”
Section: Diagnostic Ability Of Our Proposal (Test Set)mentioning
confidence: 52%